Diffusion basis spectrum imaging detects subclinical traumatic optic neuropathy in a closed-head impact mouse model of traumatic brain injury - Yang, Hsin-Chieh; Lavadi, Raj Swaroop; Sauerbeck, Andrew D.; Wallendorf, Michael; Kummer, Terrance T.; Song, Sheng-Kwei; Lin, Tsen-Hsuan (Frontiers in Neurology, 2023)
Traumatic optic neuropathy (TON) is the optic nerve injury to brain trauma leading second to visual impairment and vision loss. Current clinical visual function assessments often fail to detect TON due to disease slow progression and clinically silent lesions resulting in potentially delayed or missed treatment in patients with traumatic brain injury (TBI). Diffusion basis spectrum imaging (DBSI) is a novel imaging modality that can potentially fill this diagnostic gap. Twentytwo, 16-week-old, male mice were equally divided into a sham or TBI (induced by moderate Closed-Head Impact Model of Engineered Rotational Acceleration device) group. Briefly, mice were anesthetized with isoflurane (5% for 2.5 minutes followed by 2.5% maintenance during injury induction), had a helmet placed over the head, and were placed in a holder prior to a 2.1joule impact. Serial visual acuity (VA) assessments, using the Virtual Optometry System, and DBSI scans were performed in both groups of mice. Immunohistochemistry (IHC) and histological analysis of optic nerves was also performed after in vivo MRI. VA of the TBI mice showed unilateral or bilateral impairment. DBSI of the optic nerves exhibited bilateral involvement. Post-MRI IHC results of the optic nerves revealed axonal loss, myelin injury, axonal injury, and increased cellularity in the optic nerves of the TBI mice. Increased DBSI axon volume, decreased DBSI λ || , and elevated DBSI restricted fraction correlated with decreased SMI-312 (p = 0.0026), decreased SMI-31 (p = 0.0023), and increased DAPI density (p = 0.01), respectively, suggesting that DBSI can detect coexisting pathologies in the optic nerves of TBI mice. DBSI provides an imaging modality capable of detecting subclinical changes of indirect traumatic optic neuropathy in TBI mice.